THE ROLE OF EDUCATIONAL GAMES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Raxmonova , Nilufar (University Research Base, 2024)
This paper explores the integration of educational games in the teaching of English as a Foreign Language (TEFL). It examines how games, as a pedagogical tool, can enhance language acquisition by fostering motivation, engagement, and practical language use. The study highlights the benefits of game-based learning, including improved communication skills, increased collaboration, and enhanced cognitive development. It also addresses the challenges faced by educators in implementing games, such as resource constraints and diverse student needs. Through an analysis of both theoretical perspectives and practical examples, this paper argues that educational games can create a more interactive and effective learning environment for students of varying proficiency levels in TEFL. The findings suggest that, when carefully selected and implemented, games can significantly contribute to successful language learning.